Pengaruh Kesejahteraan Guru Komite terhadap Semangat Mengajar Guru - Marsel Nande; Sayful Amrin (JOEAI:Journal of Education and Instruction, 2018)
This study aims to determine the effect of the welfare of committee teachers on the enthusiasm of teaching high school teachers in the Komba City sub-district, East Manggarai Regency, East Nusa Tenggara. This type of research is quantitative research that emphasizes the analysis of numerical data (numbers) obtained by statistical methods with the independent variable being the welfare of the teacher and the dependent variable is the spirit of teaching. The sample was 25 high school teachers spread in 8 city schools in Komba by completing the questionnaire in full. Data collection techniques using Field Research. Data were analyzed using Pearson Product Moment and obtained r table and correlation coefficient of "r" product moment with degrees of freedom (df) = n-2 and real level (α) = 0.05. The results of this research are known r-count of 0.456, and r-table of 0.413 is also known at a significant level of 5% (0.05). Thus r-count> r-table, 0.456> 0.413. Conclusion, there is a significant influence between the level of welfare of the committee of teachers on the enthusiasm of teaching teachers. Keywords: Teacher Welfare, Spirit of Teaching